The impact of fire on the Late Paleozoic Earth system - Glasspool, Ian J.; Scott, Andrew C.; Waltham, David; Pronina, Natalia V.; Shao, Longyi (Frontiers in Plant Science, 2015)
Analyses of bulk petrographic data indicate that during the Late Paleozoic wildfires were more prevalent than at present. We propose that the development of fire systems through this interval was controlled predominantly by the elevated atmospheric oxygen concentration (p(O2)) that mass balance models predict prevailed. At higher levels of p(O2), increased fire activity would have rendered vegetation with high moisture contents more susceptible to ignition and would have facilitated continued combustion. We argue that coal petrographic data indicate that p(O2) rather than global temperatures or climate, resulted in the increased levels of wildfire activity observed during the Late Paleozoic and can therefore be used to predict it. These findings are based upon analyses of charcoal volumes in multiple coals distributed across the globe and deposited during this time period, and that were then compared with similarly diverse modern peats and Cenozoic lignites and coals. Herein, we examine the environmental and ecological factors that would have impacted fire activity and we conclude that of these factors p(O2) played the largest role in promoting fires in Late Paleozoic peat-forming environments and, by inference, ecosystems generally, when compared with their prevalence in the modern world.